Flagellin From Pseudomonas Aeruginosa Stimulates ATB0,+ Transporter for Arginine and Neutral Amino Acids in Human Airway Epithelial Cells - Barilli, Amelia; Visigalli, Rossana; Ferrari, Francesca; Borsani, Giuseppe; Dall'Asta, Valeria; Rotoli, Bianca Maria (Frontiers in Immunology, 2021)
At present, the central role played by arginine in the modulation of the inflammatory cellular responses is well-recognized, and many pro-inflammatory stimuli are known to modulate the expression and activity of its transmembrane transporters. In this regard, we have addressed the effects of bacterial flagellin from Pseudomonas aeruginosa (FLA-PA) on the uptake of the amino acid in human epithelial respiratory cells. Among the arginine transporters, only ATB0,+, y+L, and y+ were operative in bronchial epithelial Calu-3 cells under control conditions; however, only the expression and activity of ATB0,+ were stimulated upon incubation with flagellin, whereas those of systems y+L and y+ were not stimulated. As a result, this induction, in turn, led to an increase in the intracellular content of arginine without making any change to its metabolic pathway. In addition, flagellin upregulated the amount of other amino acids substrates of ATB0,+, in particular, all the essential amino acids, such as valine, isoleucine, and leucine, along with the non-essential glutamine. At the molecular level, these effects were directly referable to the stimulation of a toll-like receptor-5 (TLR5) signaling pathway and to the induction of nuclear factor-κB (NF-κB) transcription factor. An induction of ATB0,+ expression has been observed also in EpiAirway™, a model of primary human normal tracheal-bronchial epithelial cells that mimics the in vitro pseudostratified columnar epithelium of the airways. In this tissue model, the incubation with flagellin is associated with the upregulation of messenger RNAs (mRNAs) for the chemokine IL-8 and for the cytokines IL-6 and interleukin-1β (IL-1β); as for the latter, a marked secretion in the extracellular medium was also observed due to the concomitant activation of caspase-1. The overall findings indicate that, in human respiratory epithelium, flagellin promotes cellular responses associating the increase of intracellular amino acids through ATB0,+ with the activation of the inflammasome. Given the role of the ATB0,+ transporter as a delivery system for bronchodilators in human airway epithelial cells, its induction under inflammatory conditions gains particular relevance in the field of respiratory pharmacology.